Geografia eleitoral e decisão do voto: uma análise a partir do eleitorado de Guarapuava-PR - Augusto, Daniel Cirilo (2012)
Regarding Electoral Geography, this research intends to investigate events about politics of parties and election. The main objective is analyzing characteristics about voters` decision of vote in Guarapuava-PR, if the identification is with the party or with the politician. Before we discussed about Electoral Geography and Electoral Behavior where the objective was analyzing the main theories that explain electoral behavior and decision regarding the vote. Reading and analysis of main power groups` characteristics in Guarapuava were done to carry out the proposal above. Through reading and analysis, it was possible to realize that power groups influence the identification with the politician since they always do many things to get the politic power. The methodological procedures were based by questionnaires, interviews with politician and analysis of newspaper reports. The diagnostic about voters` decision of vote in Guarapuava was done starting from focus in power groups. The result of the research was that Guarapuavanos voters vote specially because identification with the politician. Politician` personal characteristics are more important than party they belong.